2011
DOI: 10.1099/mic.0.046490-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c 4 is required for siderophore expression by Legionella pneumophila, whereas cytochromes c 1 and c 5 promote intracellular infection

Abstract: A panel of cytochrome c maturation (ccm) mutants of Legionella pneumophila displayed a loss of siderophore (legiobactin) expression, as measured by both the chrome azurol S assay and a Legionella-specific bioassay. These data, coupled with the finding that ccm transcripts are expressed by wild-type bacteria grown in deferrated medium, indicate that the Ccm system promotes siderophore expression by L. pneumophila. To determine the basis of this newfound role for Ccm, we constructed and tested a set of mutants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 58 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…Recent studies have identified both LbtU as a novel, TonB-independent receptor for legiobactin and LbtC as an inner membrane, ABC-type permease that helps mediate legiobactin assimilation (13,21). We also demonstrated that cytochrome c 4 is required for optimal siderophore production, although the means by which this cytochrome promotes legiobactin expression are unclear (22). Despite these various advances in our understanding of the genetics and membrane transport of legiobactin, elucidation of the structure of the L. pneumophila siderophore has remained elusive.…”
mentioning
confidence: 87%
“…Recent studies have identified both LbtU as a novel, TonB-independent receptor for legiobactin and LbtC as an inner membrane, ABC-type permease that helps mediate legiobactin assimilation (13,21). We also demonstrated that cytochrome c 4 is required for optimal siderophore production, although the means by which this cytochrome promotes legiobactin expression are unclear (22). Despite these various advances in our understanding of the genetics and membrane transport of legiobactin, elucidation of the structure of the L. pneumophila siderophore has remained elusive.…”
mentioning
confidence: 87%
“…DRelative growth on non-iron-supplemented BCYE agar containing 10-14 mM DFX. dData previously reported (Allard et al, 2006;Yip et al, 2011). §+, Ability to utilize legiobactin-containing supernatants for growth stimulation on non-iron-supplemented BCYE agar containing 400 mM DIP at 25 u C. ||Unexplained variable phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These mutants (listed in Table 1 by numbers ranging from NU205 to NU244) had been initially identified based upon their hypersensitivity to the iron chelator EDDA in their growth media and/or their resistance to streptonigrin, an antibiotic whose toxicity requires significant levels of intracellular iron (data summarized in Table 3). Subsequent studies found that none of these mutants is impaired for the production of legiobactin (summarized in Table 3), with the exception of NU208, which had proved to contain an insertion in the cytochrome c maturation locus (Table 1) (Allard et al, 2006;Yip et al, 2011). Continuing the genetic analysis that had begun with NU208, NU216 and NU244 (Viswanathan et al, 2000(Viswanathan et al, , 2002, we performed inverse PCR and DNA sequence analysis and defined the site of the mini-Tn10 insertion in most of the ira mutants, i.e.…”
Section: Pneumophila Ira Mutants Are Not Impaired For Legiobactin mentioning
confidence: 99%
“…In addition, LbtU, LbtC and Cyc4 also play roles in iron acquisition. Cyc4 promote secretion of the legiobactin, LbtU and LbtC with their coded genes, lbtU and lbtC mediate uptake of Fe3+ legiobactin complexes in which LbtU, as a TonBindependent receptor for the siderophore specifically promotes L. pneumophila's utilization of legiobactin and likely acts as the receptor for the Legionella siderophore, LbtC involves in iron regulated [81,[83][84][85].…”
Section: The Mip Protein and Its Role In Virulencementioning
confidence: 99%